Therapeutic Efficacy of Various Formulations of Cycloferon in the Treatment of Infectious Mononucleosis in Children - D. YU. Kurmaeva; I. P. Baranova (Антибиотики и Химиотерапия, 2020)
One hundred twenty six children at the age of 4 to 7 years with infectious mononucleosis were observed. The subjects under the complex therapy were treated with cycloferon suppositoria (1st group), intramuscular cycloferon (2nd group) or placebo (3rd group). The results demonstrated similar therapeutic efficacy of the parenteral cycloferon and rectal suppositoria (a novel cycloferon formulation).